(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation: This article investigates the role of code-switching in English language classrooms, particularly in EFL (English as a Foreign Language) settings. It examines the potential advantages of incorporating students’ first language to aid comprehension and engagement, as well as the drawbacks that may hinder immersion and fluency. The study also offers practical strategies for balanced and purposeful code-switching to enhance language learning outcomes.